Socially Just Religious and Spiritual Interventions Ethical Uses of Therapeutic Power (AFTA SpringerBriefs in Family Therapy,, 2018)
This insightful work answers essential questions in family therapy by exploring the ethical use of religion and spirituality in the clinical context. Its justice-informed framework explores how to employ the spiritual as a source of resilience and empowerment as well as counter harmful spiritual and religious influences in situations that cause families and couples stress, particularly relating to gender, sexuality, race, culture, and identity. Powerful case studies show therapists and clients collaborating on meaning-making and comfort in the face of longstanding conflict, acute and chronic illness, estrangement, and loss. Coverage also explores the ethical responsibilities of determining whether beliefs are helpful or harmful to client mental health and offers guidelines for therapists navigating personal biases regarding faith. This vital text: · Spotlights the influence of an often-overlooked aspect of mental health · Provides detailed examples of religion and spirituality across diverse families and issues · Outlines practical strategies for integrating helpful aspects of clients' relationship with the sacred into treatment · Offers a framework for countering harmful aspects of clients' religious beliefs or practices · Includes interventions used with couples, parents/children, and other family units · Adds a socially just perspective on the spiritual dimension of mind/body concerns · Encourages readers' professional development and self-reflection Addressing critical issues where belief frequently takes center stage, Socially Just Religious and Spiritual Interventions is an invaluable resource for family therapists, psychotherapists, and other professionals pursuing a socially just, clinically relevant approach to spiritual and religious therapeutic integration.